2000
DOI: 10.1136/gut.46.1.9
|View full text |Cite
|
Sign up to set email alerts
|

Relative risk of dysplasia for patients with intestinal metaplasia in the distal oesophagus and in the gastric cardia

Abstract: Background-Biopsy specimens obtained from the gastro-oesophageal junction can reveal intestinal metaplasia in patients presenting for routine upper endoscopy. The site of biopsy may play a critical role in determining the dysplasia risk of a patient. Aims-To evaluate prospectively the dysplasia risk in patients with intestinal metaplasia of the distal oesophagus or within the gastric cardia. Methods-Patients with short segment Barrett's oesophagus (SSBO) and cardia intestinal metaplasia (CIM) were followed pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
111
2
5

Year Published

2002
2002
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 181 publications
(120 citation statements)
references
References 18 publications
(8 reference statements)
2
111
2
5
Order By: Relevance
“…On the other hand, Oberg et al (35) reported the development of cardiac mucosa (with some proceeding to IM) in the proximal esophagus after esophagectomy, suggesting that this is an acquired condition related to acid exposure. Interestingly, Sharma et al (16) found that there was a higher prevalence and incidence of dysplasia in their short segment BE group than in their CIM group (11.3% versus 4.6%, respectively). These data support our hypothesis that the development of BE is a progression from CIM to BE, then to dysplasia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, Oberg et al (35) reported the development of cardiac mucosa (with some proceeding to IM) in the proximal esophagus after esophagectomy, suggesting that this is an acquired condition related to acid exposure. Interestingly, Sharma et al (16) found that there was a higher prevalence and incidence of dysplasia in their short segment BE group than in their CIM group (11.3% versus 4.6%, respectively). These data support our hypothesis that the development of BE is a progression from CIM to BE, then to dysplasia.…”
Section: Discussionmentioning
confidence: 99%
“…Some suggest that it is linked to Helicobacter pylori infection (12,13), while others associate it with acid reflux (5,14,15). Another study suggests that patients with short segment BE have a higher risk for developing dysplasia than patients with CIM (16).…”
mentioning
confidence: 99%
“…For example, the length of the BE segment has been considered as a major risk factor for progression to EAC (Hameeteman et al, 1989;Miros et al, 1991;Williamson et al, 1991;Iftikhar et al, 1992;Menke-Pluymers et al, 1993;van der Burgh et al, 1996;Avidan et al, 2002) and dysplasia (Gopal et al, 2003). However, several studies have also shown that EAC occurs in short-segment BE (Hamilton et al, 1988;Schnell et al, 1992;Cameron et al, 1995;Sharma et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Similar to SSBE, the risk of development of dysplasia and adenocarcinoma in CIM is unknown. However, clinical studies suggest that the tendency for developing dysplasia or carcinoma in patients with intestinal metaplasia of the cardia is considerably lower than in BE (16,22). Consequently, patients with CIM are not usually enrolled in screening programs.…”
mentioning
confidence: 99%